A steep climb for an accused person: An examination of the courts' approach to application for further evidence. Issue 2 (3rd May 2016) - Viljoen, Tjaart; Tshehla, Boyane
Abstract: The law makes provision for further evidence to be adduced even after the completion of the trial. However, the courts only allow such further evidence in exceptional circumstances and have repeatedly stated that such power should be exercised sparingly. This entrenched approach, based on an approach established in S v de Jager, starts with a pre-disposition against the adducing of further evidence. The constitutional imperatives of a fair trial, which in turn also guide a court of appeal in determining its own processes, should be interpreted to give content to substance over processes. It is the need to give effect to these constitutional imperatives that belies the core argument of this article that the de Jager test be modified so that the inquiry starts from a premise that enquires whether the evidence will affect the outcome of the case with the other two requirements serving a subordinate role.